A panel study of sickness presence and sickness absence among secondary school students - Vegard Johansen (International Journal of Occupational Medicine and Environmental Health, 2019)
Objectives This article investigates sickness presence among secondary school students in 5 European countries. The research questions asked are: What characterizes students with high sickness presence in secondary schools? Does high sickness presence influence future sickness absence?